Robust Scheduling Method of TT＆C Resource in Satellite Network - Xiang JI; Runzi LIU; Chenhong YAO; Jianhao CHEN; Tao MU (天地一体化信息网络)
The continuous growth of satellite network scale brings great challenges to the eff ective scheduling of TT＆amp;C resources.Aff ected by weather and other factors, the performance of the satellite-ground link is of high uncertainty.In order to took into both resource utilization and task reliability, a robust scheduling method of TT＆amp;C resources was proposed.This method could arranged the start time and duration of the transmission window for TT＆amp;C tasks by the predicted the channel state distribution of satelliteground link and the task distribution in the planning period, and optimized the resource allocation scheme by backward iteration to maximized the expected profit of the tasks.The experimental results showed that compared with the traditional non-robust scheduling method, the scheduling method proposed could obtain more task profi t under diff erent channel distributions and achieve the improvement of both resource utilization and task reliability.